MIR100HG Regulates CALD1 Gene Expression by Targeting miR-142-5p to Affect the Progression of Bladder Cancer Cells in vitro, as Revealed by Transcriptome Sequencing - Zhang, Sheng; Wang, Qin; Li, Wenfeng; Chen, Jinzhong (Frontiers in Molecular Biosciences, 2022)
Background/Aim: The role of lncRNA and ceRNA networks in bladder cancer, especially the function of lncRNA-miRNA-mRNA regulatory network in bladder cancer, is still relatively small. This research mainly used lncRNA sequencing to screen hub lncRNAs and ceRNA, explore its pathogenic mechanism in bladder cancer, and search for potential diagnostic and therapeutic targets. Methods: Through high-throughput lncRNA sequencing, combined with limma package, Kaplan-Meier curve analysis, lncRNA-mRNA co-expression network, univariate Cox analysis, multivariate Cox analysis, risk model construction, PPI, GO and KEGG, WGCNA, ceRNA network, miRNA prediction and qPCR were used to analyze and screen differentially expressed lncRNAs and mRNAs. Then the effects of MIR100HG on the proliferation, migration and invasion of bladder cancer cell 5637 were evaluated by CCK-8, wound-healing and transwell. Dual luciferase reporter assay was used to validate MIR100HG/miR-142-5p and miR-142-5p/CALD1 targeting relationship, and the regulatory relationship among MIR100HG/ miR-142-5p/CALD1 expression was explored by qPCR. Results: A total of 127 differentially expressed lncRNAs and 620 differentially expressed mRNAs were screened. Through survival prognosis analysis, cox analysis, lncRNA-mRNA network, PPI and WGCNA analysis, we obtained 3 hub lncRNAs and 13 hub mRNAs, and obtained a hub regulatory axis: MIR100HG/miR-142-5p/CALD1 regulatory axis. QPCR results showed that compared with the adjacent tissues, the expression of MIR100HG and CALD1 was up-regulated, the expression of miR-142-5p was down-regulated. Moreover, the expression of MIR100HG was positively correlated with the tumor grade and clinical grade of patients with bladder cancer. Overexpression of MIR100HG can effectively promote the proliferation, migration and invasion of 5637 cells, and overexpression of MIR100HG can also inhibit the expression of miR-142-5p and promote the expression of CALD1 in 5637 cells. In addition, miR-142-5p inhibits the expression of CALD1 in bladder cancer cells through direct association, and can also reverse the proliferation activity and CALD1 expression of 5637 cells induced by overexpression of MIR100HG. Conclusion: MIR100HG regulates the expression of CALD1 by targeting miR-142-5p to inhibit the proliferation, migration and invasion of bladder cancer cells. And MIR100HG is an independent prognostic factor for bladder cancer, with the potential as a biomarker for the diagnosis and treatment of bladder cancer.